Can I Speak English in My Home?: The Role of Parents’ Support in Students’ English Learning Motivation: A Narrative Study - Farida, Lailatul; Mustofa, Mu; Elga Romadhon, M Galuh (Universitas Cokroaminoto Palopo, 2024)
This narrative study aims to explore how support at home influences students' motivation to learn English, focusing on their unique experiences and journeys. Four high school students were interviewed through semi-structured interviews. The research's findings reveal significant insights into the diverse roles that parental support plays in students' acquisition of English language skills. It was revealed that active parental involvement, including encouragement, opportunities for practice, and reinforcement of their efforts, significantly boosted students' confidence and drive to improve. Moreover, students noted significant psychological benefits derived from parental encouragement. This study provides a valuable understanding of the intricate relationship between these interpersonal factors critical to students' language development. This research underscores the need for educators and parents to recognize and nurture these interpersonal dynamics to effectively support students in their language learning endeavors.